Neurodevelopmental Outcomes of Young Children Born to HIV-Infected Mothers: A Pilot Study - McHenry, Megan S.; Oyungu, Eren; Yang, Ziyi; Ombitsa, Ananda R.; Cherop, Cleophas; Vreeman, Rachel C. (Frontiers in Pediatrics, 2021)
Introduction: Over 15 million children who were exposed to HIV perinatally but uninfected (HEU) are alive globally, and they are faced with multiple risk factors for poor neurodevelopment. While children who are HIV-infected (HIV+) appear to have worse neurodevelopmental scores compared to children unexposed and uninfected with HIV (HUU), the evidence is mixed in children who are HEU. This small descriptive pilot study aimed to compare neurodevelopmental scores of children who are HIV+, HEU, and HUU in Kenya. Methods: This cross-sectional pilot study included children ages 18-36 months who were HIV+, HEU, or HUU. Neurodevelopment was assessed, along with sociodemographic, lab, and growth data. Statistical analysis included descriptive statistics, one-way ANOVA, chi-squared, and adjusted linear regression models. Results: 172 were included (n=24 HIV+; n=74 HEU; n=74 HUU). Mothers of children who were HEU experienced more depressive symptoms (p<0.001). The only neurodevelopmental differences were found among groups was that children who were HIV+ had higher receptive language scores (p=0.007). Lower height-for-age z-scores and being left home alone were associated with worse neurodevelopmental scores. Conclusions: Being stunted, left completely alone for at least an hour within the last week, and having higher sociodemographic status were associated with worse neurodevelopmental scores. The higher levels of depressive symptoms within mothers of children who are HEU warrants further investigation.